2022
DOI: 10.3389/fphar.2022.794042
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolomics Coupling With Clinical Laboratory Indicators Reveal Taxonomic Features of Leukemia

Abstract: Metabolic abnormality has been considered to be the seventh characteristic in cancer cells. The potential prospect of using serum biomarkers metabolites to differentiate ALL from AML remains unclear. The purpose of our study is to probe whether the differences in metabolomics are related to clinical laboratory-related indicators. We used LC-MS-based metabolomics analysis to study 50 peripheral blood samples of leukemia patients from a single center. Then Chi-square test and T test were used to analyze the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
1
2
0
1
Order By: Relevance
“…Though major cancer-related changes in cellular metabolism are common for malignant cells (29, 30), specific differences could be observed when metabolic profiles of serum/plasma are compared among patients with different types of cancer. For example, differences in serum levels of certain amino acids and lipids were reported in patients with different leukemias (31). Here we observed several differences in serum metabolome patterns among four types of solid cancers.…”
Section: Discussionsupporting
confidence: 55%
“…Though major cancer-related changes in cellular metabolism are common for malignant cells (29, 30), specific differences could be observed when metabolic profiles of serum/plasma are compared among patients with different types of cancer. For example, differences in serum levels of certain amino acids and lipids were reported in patients with different leukemias (31). Here we observed several differences in serum metabolome patterns among four types of solid cancers.…”
Section: Discussionsupporting
confidence: 55%
“…FLT3-ITD + AML is one of the most aggressive commonly occurring mutations observed in AML patients with bad prognosis. Altered metabolomics and dysregulated miRNA profiles are characteristics observed in FLT3-ITD AML patients ( Wallace and O'Connell, 2017 ; Lo Presti et al, 2021 ; Kreitz et al, 2019 ; Musharraf et al, 2016 ; Wang et al, 2019 ; Xiong et al, 2022 ). Numerous studies have found links between miRNAs and key genes involved in metabolism ( Hatziapostolou et al, 2013 ) in different cancer models; however, little is known whether altered metabolism can cause dysregulation of miRNA expression in AML, or other cancer settings.…”
Section: Discussionmentioning
confidence: 99%
“…Аутоиммунное воспаление манифестируя в детском возрасте, имеет склонность к формированию синтропий и множественных осложнений, влияющих на качество и продолжительность жизни пациента во взрослом возрасте [1,2]. Лимфопролиферативное воспаление у детей с одной стороны в настоящее время значительно лучше контролируется таргетными противоопухолевыми препаратами, с другой стороны, существование гетерогенного клеточного микроокружения опухоли, резистентные формы рака, развитие отдаленных осложнений в отсутствии первичного очага и тяжелых краткосрочных осложнений на фоне глубокой иммуносупрессии и генерализации микробного компонента воспаления требует уточнения генетических механизмов цитокиновой регуляции в детском возрасте [3][4][5]. Микробное воспаление при муковисцидозе имеет прогрессирующий характер и приводит к раннему снижению функции легких у детей, являясь основной причиной для трансплантации органов, а также приводит к снижению эффективности таргетной терапии [6,7], а при пиелонефрите у детей реализуется в хроническую болезнь почек, которая не имеет обратного развития и характеризуется прогредиентным течением [8][9][10][11].…”
Section: актуальностьunclassified